Antioxidant Profile in Pineapple Peel Fermentation by Lactobacillus plantarum and Lactobacillus casei - Sri Hartini; Margareta N. Cahyanti; Dewi K. A. Kusumahastuti; Indah T. Susilowati; Y. M. Anggara Mahardika (Postgraduate, University of Mataram, 2024)
Pineapple peels are a potential food waste capable of being repurposed as a substrate for producing high-antioxidant probiotic beverages. Therefore, this study aimed to determine the feasibility of using pineapple peels as a substrate for producing high-antioxidant probiotic beverages through fermentation by Lactobacillus plantarum and Lactobacillus casei. Pineapple peels juice was fermented for 48 hours and the growth of microorganisms, reducing sugars, pH, titratable acid, polyphenol compounds, and antioxidant activity were periodically analyzed. The results showed that after 24 hours, the growth of L. plantarum and L. casei gradually slowed down. As fermentation time increased, the levels of reducing sugars and the pH decreased. L. casei reached the highest titratable acidity of 0.90% equivalent to lactic acid after 48 hours of fermentation, while L. plantarum reached 1.21%. The percentage of radical inhibition and phenolic compound increased between 9 and 30 hours of fermentation. The highest inhibition activity of 39% was achieved after 30 hours of fermentation for L. casei, while for L. plantarum, it reached 55% after 9 hours. This study showed that pineapple peels could produce probiotic beverages with high antioxidant. It was a suitable alternative for vegetarians or individuals who were allergic to dairy products.